Alpis Graia (col du Petit-Saint-Bernard, Savoie et Val d’Aoste) : découvertes anciennes et recherches récentes - Sylvie Crogiez-Pétrequin (Gallia)
Recent work on Roman remains found in the Petit-Saint-Bernard pass has shown that one of the buildings (the West building) could be considered as a casa retica of the Roman era, a half-buried habitat that was traditional in the alpine region. It is on this building that the study primarily focuses, exploring past excavations, restorations, construction techniques and their adaptation to the environment, and chronologies. It also shows that all the buildings in the pass had a purpose related to the cursus publicus, Imperial Rome’s official transportation service.